Technical Vocational Education in the Philippines for Sustainable Development - Kilag, Osias Kit T.; Mag-aso, Japeth N.; Poloyapoy, Karl Brian M.; Gamboa, Ann Carmel H.; Mantua, Angel Magdalene V.; Rivamonte, Wilma D. (PT. Antis International Publisher, 2024)
This research aims to investigate the role of Technical and Vocational Education (TVE) in promoting sustainable development in the Philippines. A review of related literature was conducted to identify best practices and strategies for promoting the development of the TVE sector. The findings of this research suggest that updating curricula, investment in infrastructure and technology, and a stronger emphasis on lifelong learning can help to promote sustainable development in the Philippines. Additionally, the integration of green skills and environmental education and partnerships with industry can play a crucial role in promoting sustainable development. This research highlights the importance of addressing the challenges facing the TVE sector, including the need for innovative pedagogical approaches and investment in infrastructure and technology. The government, educators, and the private sector have a critical role to play in promoting the development of the TVE sector and ensuring its continued contribution to sustainable development in the Philippines.